Adrenal oncocytic pheochromocytoma with functionality in a neurofibromatosis patient: A case report - Kenneth A. Iczkowski, MD; Douglas B. Evans, MD; Saul M. Suster, MD (Elsevier, 2018)
Background: There are 4 prior reports of oncocytic pheochromocytoma of the adrenal. It may histologically resemble cortical carcinoma, which also can have oncocytic cells. Case presentation: We report a 54-year-old male with neurofibromatosis 1 who had an endocrinologically functional, 13.5 cm tumor. Histology showed mostly oncocytic cells. An adrenalectomy showed that the tumor had capsular and vascular invasion. Symptoms were cured by surgery. A cortical carcinoma with oncocytic change was initially favored, but the clinical history together with immunostain results were consistent with pheochromocytoma with oncocytic change. Conclusions: In conclusion, the clinical history was crucial to the diagnosis. This is the first tumor of this type in a neurofibromatosis patient and the first in which functional effects were caused.